2016
DOI: 10.1111/wvn.12154
|View full text |Cite
|
Sign up to set email alerts
|

Educating Family Caregivers for Older Adults About Delirium: A Systematic Review

Abstract: Background: Delirium in older adults is considered a medical emergency; it contributes to a cascade of functional decline and to increased mortality. Early recognition of delirium symptoms is critical to prevent these negative consequences. Family caregivers who are educated about delirium could partner with nurses and other healthcare professionals in early recognition of delirium symptoms. Before implementing such partnership models, it is important to examine the effectiveness of educating family caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…For this reason, burden should be assessed in all caregivers of and patients with delirium. As with ADRD, caregiver and peer support programs, case management, counseling, education, and long‐term multicomponent programs should be explored as potential approaches to decrease caregiver distress in delirium. The caregiver interventions for delirium will need to be tailored to specific caregiver burden dimensions, and will likely vary widely among caregivers of patients with or without ADRD.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, burden should be assessed in all caregivers of and patients with delirium. As with ADRD, caregiver and peer support programs, case management, counseling, education, and long‐term multicomponent programs should be explored as potential approaches to decrease caregiver distress in delirium. The caregiver interventions for delirium will need to be tailored to specific caregiver burden dimensions, and will likely vary widely among caregivers of patients with or without ADRD.…”
Section: Discussionmentioning
confidence: 99%
“…However, support services after the recovery of delirium would also prove beneficial as there are evidences of recurrence. Providing brochures that discuss the aspects addressed above and non‐pharmacological interventions (for instance, reorienting and reassuring the older adult, bringing familiar objects from home) that might help in reducing the incidence and prevalence of delirium and in caring for the older adult with delirium would be helpful for family caregivers to refer to whenever in need (Bull, Boaz, & Jerme, 2016; Fong et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These interventions also improved older adults performance on instrumental activities of daily living, family caregivers knowledge of delirium and family caregivers preparedness to support older adults. Other studies have shown that family caregivers experienced less anxiety and presented fewer signs of depression throughout the care episode (Boltz et al, ; Bull, Boaz, & Jermé, ; Calvo et al, ; Lundstrom et al, ). In a study assessing the feasibility of nurses and family caregivers partnering to prevent delirium in hospitalized older adults, it was found that nurse and family caregiver knowledge of delirium increased significantly post‐intervention and that participants demonstrated significantly more respect, collaboration, and mutual support (Rosenbloom & Fick, ).…”
Section: Introductionmentioning
confidence: 94%
“…care episode (Boltz et al, 2014;Bull, Boaz, & Jermé, 2016;Calvo et al, 2012;Lundstrom et al, 2005). In a study assessing the feasibility of nurses and family caregivers partnering to prevent delirium in hospitalized older adults, it was found that nurse and family caregiver knowledge of delirium increased significantly post-intervention and that participants demonstrated significantly more respect, collaboration, and mutual support (Rosenbloom & Fick, 2014).…”
Section: Introductionmentioning
confidence: 99%